2011
DOI: 10.1002/smj.1946
|View full text |Cite
|
Sign up to set email alerts
|

The impact of current and founding institutions on strength of competitive aspirations in transition economies

Abstract: Northian institutional theory argues that firms adapt to their current institutional environments. Organizational imprinting theory argues that firms will be constrained by their founding institutional environments. We explore the combined influence of these two institutional environments on the strength of competitive aspirations using a unique dataset of firms in the shifted institutional environment of Central European transition economies. Our results indicate founding institutional environments temper ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 52 publications
1
81
0
Order By: Relevance
“…Such fundamental changes span political, legal, social and economic institutions and involve two key features: reforming institutions to improve market development and the enforcement of rules (institutional reforms or development) and opening markets internationally (international openness) (Williamson, 2000). The level of international openness and degree of institutional development or reforms vary considerably across countries (Chan et al, 2008;Makino et al, 2004;Shinkle & Kriauciunas, 2012). Such cross-country variations are driven by both public institutions (judicial systems and political processes) and private institutions (corporate accountability), which may be formal (such as laws) and informal (such as norms) (North, 1990;Peng, 2003;Williamson, 2000).…”
Section: Institutional Reforms and International Openness Across Cee mentioning
confidence: 99%
“…Such fundamental changes span political, legal, social and economic institutions and involve two key features: reforming institutions to improve market development and the enforcement of rules (institutional reforms or development) and opening markets internationally (international openness) (Williamson, 2000). The level of international openness and degree of institutional development or reforms vary considerably across countries (Chan et al, 2008;Makino et al, 2004;Shinkle & Kriauciunas, 2012). Such cross-country variations are driven by both public institutions (judicial systems and political processes) and private institutions (corporate accountability), which may be formal (such as laws) and informal (such as norms) (North, 1990;Peng, 2003;Williamson, 2000).…”
Section: Institutional Reforms and International Openness Across Cee mentioning
confidence: 99%
“…These studies show that the broader economic system in which an organization is founded leaves a strong imprint, making post-transition adaptation difficult for organizations founded in a socialist regime. For example, research in Eastern Europe suggests that firm-specific capabilities and knowledge resources developed to meet the needs of one economic system are persistent and prove to be era-specific such that these "socialist imprints" adversely affect knowledge routines as well as competitive aspirations after the economic transition (Kogut & Zander, 2000;Kriauciunas & Kale, 2006;Shinkle & Kriauciunas, 2012). In China, studies have found that older firms, which were shaped more profoundly by the Communist bureaucracy, have deeply entrenched structures and vested interests and are less likely to adopt new governance practices (Marquis & Qian, 2013;Peng, 2004).…”
Section: Imprints Of Economic and Technological Conditions On Organizmentioning
confidence: 99%
“…The "institution-based view of strategy" label was first advocated by me in the Asia Pacific Journal of Management in 2002. While I can claim credit for coining this expression, institution-based research in strategy, organization and IB is a broad scholarly movement with numerous participants (Ahn & York, 2011;Ahuja & Yayavaram, 2011;Carney, Gedajlovic, & Yang, 2009;Chari & David, 2012;Dau, 2012;Hoskisson, Wright, Filatotchev, & Peng, 2013;Khoury & Peng, 2011;Kim, Kim, & Hoskisson, 2010;Liu, Yang, & Zhang, 2012;Lu, Tsang, & Peng, 2008;Mahlich, 2010;Meyer, Estrin, Bhaumik, & Peng, 2009;Meyer & Peng, 2005;Peng, 2003Peng, , 2012Peng, , 2013Pinkse & Kolk, 2012;Ritchie & Melnyk, 2011;Shinkle & Kriauciunas, 2012). While institutionally oriented scholars are naturally interested in advancing this view, it is interesting to note that a leading IB scholar John Dunning, who was not known to be an "institutionalist" and whose career spanned five decades, strongly promoted the institution-based view toward the end of his career (Dunning, 2004;Dunning & Lundan, 2008).…”
mentioning
confidence: 99%